Upaya Dan Peran Seorang Guru Dalam Mengatasi Siswa Bermasalah - Azman, Zainal; Helandri, Joni (El-Ghiroh : Jurnal Studi Keislaman, 2022)
One of the efforts of an educator in creating a conducive teaching and learning atmosphere or class that gives a pleasant impression for students in listening and understanding the content of the subject matter explained by a teacher. Not infrequently also in the learning process there are various kinds of problems in children ranging from falling asleep during class hours, the lack of neatness of students, lack of uniform attributes, for example not cursing ties, belts and socks. In more serious problems, sometimes students can act out of bounds such as student delinquency and lack of student courtesy to the teacher. The problems arise from internal and external factors. Strategies in creating an effective and conducive learning environment, the role of the teacher here is not the same as being required to teach a material but the teacher must be able to control and coordinate the class and students, so it is necessary for the teacher's role in it to be able to direct students to things that better reflect students such as biological children and pay attention to behavior and a teacher must be fair in making decisions so that there is no jealousy among other students. A teacher should pay more attention to students like their parents. The approach taken by a teacher is a behavioristic, cognitive, and humanistic approach.